How low-achieving German youth beat the odds and gain access to vocational training : insights from within-group variation - Solga, Heike [Verfasser]; Kohlrausch, Bettina [Verfasser] (My University, 2013)
"In this article, we study differences within the group of low-achieving school leavers, asking who among these disadvantaged youth is successful in entering vocational training in Germany, and why. We pay particular attention to the displacement mechanism by investigating under which conditions non-cognitive skills and personality traits are important for finding apprenticeships. Second, we specify how the mechanism of statistical discrimination works with regard to low-achieving youth. We use a unique set of German longitudinal data on school leavers who attended a lower secondary school (Hauptschule). Our main findings are non-cognitive skills, if observable before hiring, have a stronger impact on the training opportunities of less-educated youth than their grades in mathematics and German. Furthermore, extended internships completed while in school-and thus, employers' first-hand experiences with less-educated young persons-increase these youth's training opportunities." (Autorenreferat; BIBB-Doku)

"Wer die Hauptschule mit schlechten Noten oder ohne Abschluss verlässt, hat in Deutschland kaum Aussicht auf einen Ausbildungsplatz. Die Autorinnen fragen in ihrem Beitrag, warum es trotzdem einigen leistungsschwachen Schülern gelingt, eine Lehrstelle zu finden, während andere scheitern. Die Forscherinnen werten Daten einer Schülerbefragung in Niedersachsen aus und zeigen, welche Rolle nicht kognitive Fähigkeiten und Persönlichkeitsmerkmale bei der Lehrstellensuche spielen. Die Ergebnisse: Lernmotivation, Sozialkompetenzen und Arbeitstugenden haben einen größeren Einfluss als Mathematik- und Deutschnoten, sofern die Betriebe die Gelegenheit haben, die Schüler vor der Rekrutierung kennenzulernen. Die Chancen auf eine Ausbildung steigen außerdem, wenn den Schülern über Praktika eine frühe Anbindung an einen Betrieb gelingt." (WZB; BIBB-Doku)
Keywords: P 2.1.3 Hauptschulabschluss; S 1.6.1 Praktika; Hauptschüler; Absolvent; Sozialkompetenz; Persönlichkeitsmerkmal; Ausbildungschance; Betriebspraktikum